Strategi Manajemen Konflik untuk Meningkatkan Produktivitas Lembaga Pendidikan Islam - Rika Fadilatul Laila; Salisa Indah Aini; Sabila Sherinata Mayandari; Mu’alimin Mu’alimin (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Islamic educational institutions often face conflicts arising from misalignment between individual goals and institutional objectives, ineffective communication, and competition over resource utilization. Such conflicts, if not properly managed, can hinder organizational productivity. However, conflict management based on Islamic values, such as open dialogue, clarification, compromise, and accommodation, has proven to transform conflicts into opportunities for innovation, strengthen collaboration, and enhance productivity. This study adopts a literature review approach to analyze conflict management strategies aimed at improving the productivity of Islamic educational institutions. The findings reveal that a constructive approach to conflict management not only resolves issues but also fosters a harmonious and inclusive work environment. By employing strategies such as negotiation, mediation, and collaboration, conflicts can become drivers of innovation and organizational performance improvement. Moreover, the role of wise leadership in establishing policies based on Islamic values is crucial for creating a synergistic, productive, and competitive organization. This research is expected to serve as a reference for developing sustainable and effective conflict management strategies in Islamic educational institutions.